8A.07: NON-INVASIVE ASSESSMENT OF HAEMODYNAMICS IN RESISTANT HYPERTENSION. (June 2015) - Kintis, K.; Tsioufis, C.; Dimitriadis, K.; Kalos, T.; Liatakis, I.; Andrikou, E.; Koutra, E.; Thomopoulos, C.; Makris, T.; Tousoulis, D.
Abstract : Objective: Hypertension is a multisystem disease in which the kidney plays a key role in long term regulation of blood pressure and the development of hypertension. The aim of this study was to evaluate the role of intrarenal resistance indices in the renal interlobular arteries measured by Doppler ultrasound in resistant hypertensive patients. Design and method: We studied 50 patients with resistant hypertension (RH) [age: 61 ± 11 years, 31 males, office blood pressure (BP): 163/89 ± 24/15 mmHg, under 4.2 ± 0.5 drugs] and 50 hypertensive patients controlled on three or less drugs [age: 59 ± 9 years, 26 males, BP: 131/79 ± 9/8 mmHg, under 2.2 ± 0.3 drugs] that underwent transthoracic echocardiographic study for determination of mitral annular early diastolic velocity (E/e') and blood sampling for assessment of metabolic profile. Moreover, data on renal resistive index (RRI), obtained by Doppler ultrasound sampling of the intrarenal arteries, were retrospectively analyzed. Results: Hypertensives with RH compared to those without RH exhibited higher RRI by 0.078 (p < 0.001) and E/e' values by 3.1 (p < 0.001). In the entire study population, RRI was negatively related to office diastolic BP (r = −0.239, p < 0.05), while it was positively associated with office systolic BP (r = 0.310, p < 0.05), office PP (r = 0.583, p < 0.01), age (r = 0.322, r < 0.001), and LVMI (height) (r = 0.283, p < 0.001). Systolic BP (beta 0.864, p < 0.001) and diastolic BP (beta −0.907, p < 0.001) were the only independent predictors of RRI in linear regression analysis, while according to multivariate logistic regression analysis, the major factors influencing whether a person reported having RH were RRI, E/e', duration of hypertension, and age. Conclusions: Increased renal and cardiac haemodynamics, as reflected by increased vascular resistance of intrarenal arteries and E/e', are associated closely with the presence of RH. These findings imply that RRI and E/e' values should be taken into account for the prediction of insufficient control of BP in hypertensive patients.